TECHNICAL ANALYSIS PERFORMANCE MEASUREMENT IN INDONESIAN STOCT MARKET - , Felix Bram Samora, Prof. Dr. Eduardus Tandelilin, MBA, CWM ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research entitled âTechnical Analysis Performance Measurement in Indonesian Stock Marketâ is purposed to measure the performance of technical analysis approach in Indonesian stock market during 5 years period from 2006 until 2011. The performance of technical analysis was compared by buy and hold strategy performance as the benchmark. The combination trading strategy which uses three technical indicators which are moving average, Bollinger band and candlestick engulfing pattern is used as technical analysis approach. The three indicators are combined so that there are six combinations that were used. The first combination is using only moving average indicator, the second combination use candlestick engulfing pattern only, the third combination use moving average and Bollinger band, the fourth combination use moving average and candlestick engulfing pattern, the fifth combination use candlestick engulfing pattern and Bollinger band and the sixth combination use all of the three indicators. After all of the combination strategies were tested, the best strategy for each stock then selected as the optimum strategy. The result of this optimum combination strategy then compared with buy and holds strategy return to answer the research question. The strategies were modeled using Meta Trader 4 software and applied to 17 stock sample that enlisted in LQ-45 during February 2008 until July 2011. The research result indicates that the combination trading strategy with 332.1% total return can outperform the buy and hold strategy of 114% return. The two returns were compared statistically using t-test significance with 95% confidence interval and the result indicate that the combination trading strategy return is statistically higher than buy and hold strategy with 0.00047 significance value.